Advancements in Material Utilization for Prosthetic Lower Limb Knee Joints: Enhancing Performance and User Experience - Shriwas, Anand Kumar; Khute, Nikhileswar (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2025)
Abstract - The prosthetic lower limb knee joint is a critical component for restoring mobility and improving the quality of life for individuals with lower limb amputations. This paper provides a comprehensive review of the latest advancements in material utilization for these vital devices.  It explores the modern application of metals, polymers, composites and the emerging search for smart and biomimetic materials, highlighting their impact on the biomechanical performance, durability, weight, user comfort, and overall functionality of prosthetic knee joints. Furthermore, it examines the role of advanced manufacturing techniques, such as 3D printing, in enabling innovative material applications and personalized prosthetic options. The paper concludes by discussing the ongoing challenges and future directions in material research aimed at optimizing prosthetic knee joint technology for enhanced user outcomes. Key Words: Prosthetic Knee Joint, Materials, Advanced Materials, Smart Materials, Biomimetic Materials, 3D Printing, Durability, User Experience.